DHCED and DHCOD Technique of Visual Cryptography Scheme for Encrypted and Decryption - Ponnarasi, S; Rajendran, T (International Journal of Computer Sciences and Engineering, 2025)
Visual Cryptography is a new cryptographic technique which allows visual information (pictures, text, etc.) to be encrypted in such some way that the decipherment will be performed by human, with none decipherment algorithmic rule. Here we have a tendency to propose a knowledge activity in halftone pictures victimisation conjugate ordered video digitizing (DHCOD) algorithmic rule that could be a changed version of information activity in halftone pictures victimisation conjugate error diffusion technique (DHCED). We have a tendency to use this DHOCD algorithmic rule for proposing a brand new 3 part visual cryptography theme. DHCOD technique is employed to cover Associate in Nursing binary visual pattern in 2 or additional ordered dither halftone pictures, which may be from identical or completely different multi-tone pictures. In projected theme we have a tendency to shall generate the shares victimisation basic visual cryptography model so imbed them into a canopy image employing a DHCOD technique, so the shares are going to be safer and pregnant